The Influence Has Had Globalization and Its Trends in the National Economy (2016)
The present work was identifying the economic development that has had Colombia across the years departing from the differentiation of exports and imports presented from the year 1990 up to 2015, indicating the benefits and disadvantages that they have presented in Colombia on having opened his borders and to be allowed to be a part of the Globalization appearing that this one not only influences the economy but in other sectors that take us to the competitiveness with other countries.